Antimycobacterial labdane diterpenes from leucas stelligera - Kulkarni, Roshan R.; Shurpali, Ketaki; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Journal of Natural Products, 2013)
Phytochemical investigation of the acetone extract of the aerial parts of Leucas stelligera afforded four new compounds (1-4) belonging to the labdane diterpene series as well as two known flavones, velutin (5) and chrysoeriol (6). Structure elucidation of the new compounds was carried out using ID and 2D NMR spectroscopic data and single-crystal X-ray crystallography of compound 1. Compounds 1-4 exhibited selective antimycobacterial activity against Mycobacterium tuberculosis with IC50 values in the range 5.02-9.80 mu g/mL.